PARENTAL EXPRESSED EMOTION (EE) PREDICTS PSYCHOSOCIAL PROBLEMS IN ADOLESCENTS: A LITERATURE REVIEW - Andi Buanasari; Esrom Kanine (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2020)
Background: Psychosocial problems in adolescents are often associated with difficulty in achieving their developmental tasks sense of identity that lead them to the role of confusion. The parents play an important role in assiting and supporting the adolescents to accomplish their developmental task during this age but sometimes the emotions, attitudes or behaviors shown by parents (Expressed Emotion/ EE) were actually considered to be factors that influence the psychosocial problems in adolescents. Aim: To describe the correlation between EE in parents and psychosocial problems in adolescents. Methods: A literature review was conducted to collect English-language articles form online database such as Proquest, PubMed, Sagepub, Science Direct and Taylor & Francis about the correlation between EE and psychosocial problems in adolescents from 1985 to 2020. Results: Adolescents with psychosocial problems tend to have parents with high EE and Criticism apparently became the most influential aspect in affecting psychosocial problems in Adolescents Conclusion: It is important to strengthen education and therapy for parents to decrease critical parenting style as an effort to promote adolescent mental health.